2015
DOI: 10.1016/j.sbspro.2015.07.361
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing Total Quality Management

Abstract: The purpose of this study were to investigate the factors influencing total quality management modeling for a sub-district municipality, and to create a suitable total quality management model for a sub-district municipality. This research utilized a qualitative method by use of in-depth interviews. The respondents were 30 leaders from the sub-district municipality offices. Seven factors were used in the measurement, which included [i] leadership; [ii] training; [iii] organizational structure; [iv] communicati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…There are several papers discussing the effect of TQM on manufacturing systems performance; for instance Cetindere et al [30] have reported the TQM impact on the economic and financial performance and Bon and Mustafa [31] have reported the effect of TQM on the innovation process; however, these benefits are due to certain activities associated with the design and planning of the product, as well as the production process; Taylor and Wright [32] have carried out a longitudinal study with the CSF of TQM over time, where these have changed through time and as time has passed by, they have increased; and recently Singh, et al [33] have reported the main CSF that managers should mainly focus in order to implement TQM correctly, concluding that these are: organizational leadership, customer relationship and satisfaction, HR orientation, strategic planning and development, raw materials quality, and relationships with suppliers. On the other hand, Suwandej [34] has reported that the CSF of TQM are: leadership, training, organizational structure, communication, employee incentives, measurement systems, and evaluation of executed projects, as well as improvement teams.…”
Section: The Critical Sucess Factors Of Tqmmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several papers discussing the effect of TQM on manufacturing systems performance; for instance Cetindere et al [30] have reported the TQM impact on the economic and financial performance and Bon and Mustafa [31] have reported the effect of TQM on the innovation process; however, these benefits are due to certain activities associated with the design and planning of the product, as well as the production process; Taylor and Wright [32] have carried out a longitudinal study with the CSF of TQM over time, where these have changed through time and as time has passed by, they have increased; and recently Singh, et al [33] have reported the main CSF that managers should mainly focus in order to implement TQM correctly, concluding that these are: organizational leadership, customer relationship and satisfaction, HR orientation, strategic planning and development, raw materials quality, and relationships with suppliers. On the other hand, Suwandej [34] has reported that the CSF of TQM are: leadership, training, organizational structure, communication, employee incentives, measurement systems, and evaluation of executed projects, as well as improvement teams.…”
Section: The Critical Sucess Factors Of Tqmmentioning
confidence: 99%
“…From the list by Singh, Kumar and Singh [33] and Suwandej [34], it is observed that many CFS of TQM are associated with HR, for instance the level of managerial commitment, where senior managers are the ones who must define the quality objectives, integrating them into strategic plans, and establish their priority. Managers should also allocate economic resources for TQM programs, such as kaizen, continuous improvement, and training for operators.…”
Section: The Critical Sucess Factors Of Tqmmentioning
confidence: 99%
“…A study by Gimenez-Espin et al (2013) finds empirical evidence that organizational culture should fit best with a quality management system in order to achieve improved business performance. Furthermore, other researchers (Suwandej 2015;Mazher et al 2015;Pimentel and Major 2016) argue that "Organizational characteristics" is one of the significant factors for controlling the quality management system. The above mentioned discussions lead us to suppose that 'organizational characteristics' is an important variable in determining the implementation of quality management system in business.…”
Section: Organizational Characteristics (Och)mentioning
confidence: 99%
“…Hence, organizations attempt to implement quality management system in order to gain competitive advantages and then achieve successes for business. A number of previous studies have investigated the effect of factors on the successful implementation of quality management systems (Claver et al 2003;Mellahi and Eyuboglu 2001;Quazi et al 1998;Warwood and Roberts 2004;Yeh et al 2012;Yusof and Aspinwall 2000;Fayzollahi et al 2013;Suwandej 2015;Bolatan et al 2016;Mazher et al 2015;Pimentel and Major 2016). Nonetheless, only few studies have made investigation on factors that determine the implementation of quality management systems.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it can guide teachers in implementing the learning process. TQM, as a management process, has been widely applied in the industrial sector, then the system improvement in the production process [5], improves the management system [6], as well as to increase its company profit [7].…”
Section: Introductionmentioning
confidence: 99%